Choux Paste Quality With Canna Flour Substitution - Syukra, Elfa; Elida, Elida; Kasmita, Kasmita; Anggraini, Ezi (Universitas Negeri Padang, 2024)
The purpose of this study was to analyze the effect of canna flour substitution as much 25%, 35% and 45% on quality of choux paste in terms of shape, color, aroma, texture and taste. This type of research is an true experiment with the completely randomized design method (RAL) and three repeats. The source of data in this study was obtained from 3 expert panelists. The tool used in taking data is in the form of questionnaires containing questions about the quality of choux paste. The data was analyzed using ANAVA, if Fcount ≥ Ftabel then continued with the Duncan test. The results showed that there was a significant effect choux paste of canna flour substitution between 25%, 35% and 45% on the quality of thes, namely on the quality of the dark brown color of the out, and light brown on the inside of the choux paste, the aroma of canna scented choux paste. The quality of the shape (round, neat and hollow), crunchy texture on the outside and soft on the inside, savory taste has no effect on the quality of the choux paste. The best canna flour choux paste quality test results are in X3 treatment with canna flour substitution as much as 45%.Keywords: Canna Flour, Choux Paste, Quality